Physical Activity Levels, Anthropometric Characteristics, and Attitudes of Nationalism at State High School Paloh on the Indonesia-Malaysia Border - Fachrurrozi Bafadal, Muhammad; Hidasari, Fitriana Puspa; Haetami, Mimi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2021)
The purpose of this study was to investigate the level of physical activity, anthropometric characteristics, and attitudes of nationalism among secondary school children in the Indonesia-Malaysia border region (Border Aruk/Sajingan, Sambas Regency). The method used in this research is a quantitative descriptive study in the form of a survey. The population and sample used are students at the high school level in the border area. Participants in this study were based on the following criteria: 1) Willingness to be a participant in the study, and 2) Present at the time of field data collection. The instrument used in this research is the International Physical Activity Questionnaire (IPAQ) Short Form version to measure the variable level of physical activity. Anthropometric measurements use eleven parameters. Assessment of the attitude of Nationalism using a questionnaire. Based on the results of the study, the level of physical activity of students at the border showed a moderate category. Meanwhile, anthropometric measurements show varying results, the measurement results can be categorized into three types based on these results, namely: ectomorph, mesomorph, and endomorph. Overall in the attitude of nationalism of the Indonesian-Malaysian border students in Paloh sub-district, Sambas district, shows that the dominant border students are in the good category in interpreting nationalism..